PILIHAN RASIONAL ISTRI MENGGUGAT CERAI SUAMI (STUDI KASUS KECAMATAN BINA WIDYA KOTA PEKANBARU - Filda Iis Dwi Lestari; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Marriage is a sacred bond between two individuals who love each other and are bound by a legal bond of marriage, but not a few married couples divorce, whether it's a lawsuit for divorce or a lawsuit for divorce. Divorce as a result of poor marital adjustment and occurs when a husband and wife are no longer able to find a solution to a problem that satisfies both parties. At the present time there are many cases of wives suing their husbands for divorce or contesting divorces, this happens because of a change in mindset that occurs in divorce not only husbands have the right to determine divorce but women are also entitled and have the same rights as men. This thought arose not without reason but because there was rational thinking as there was no rationality in the household. Apart from that, in a divorce, there must be a cause, so that in this study it will be examined further about the factors that cause a wife to sue her husband for divorce and how to sue her husband for divorce as a rational choice. This research was conducted in Bina Widya District, Pekanbaru City. The informants in this study were 5 informants. The method in this research is descriptive qualitative. Sources of data namely through observation and interviews. The results of this study indicate that there are many factors that cause divorce, such as disputes and constant fighting in the household, husbands leaving their wives, and economic factors. Then the wife's choice in suing her husband for divorce is ripe, it can be seen from the wife without hesitation in suing even though she already has children, meaning that the wife is ready to use her power to sue her husband, in accordance with Coleman's theory statement where this theory emphasizes that an individual commits an action which the action will take advantage of. the resources he has to achieve a goal. Keywords : Divorce, Rational Choice.